Manajemen Haji dan Umrah Indonesia: Problematika Kebijakan dan Peningkatan Tata Kelola - Dirwanto (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper outlines that the implementation of hajj and umrah pilgrimage in Indonesia faces various complex challenges that require comprehensive policy transformation and governance reform. This policy article analyzes the main problems in Indonesian hajj and umrah management, including long queues of hajj candidates reaching 20-30 years, imbalanced quota distribution among provinces, weak PPIU supervision, and low quality of manasik guidance. This paper uses qualitative writing methods with comprehensive document analysis and literature study approaches. The analysis uses the Urgency, Seriousness, Growth (USG) approach developed by Bryson (2018) to determine problem priorities, with William N. Dunn's policy alternative evaluation method based on effectiveness, efficiency, feasibility, sustainability, and political feasibility criteria. The theoretical foundation integrates Public Service Management Theory, Queue Management Theory, Good Governance, and Service Quality Model. Five policy alternatives are analyzed, with the Integrated National Hajj Management System (SIMHAJI) obtaining the highest score (22). The results show that SIMHAJI is the optimal solution because it can address root problems systemically, increase operational efficiency by up to 31%, and strengthen transparency and accountability in hajj-umrah implementation. The main conclusion mentions the need for comprehensive digital transformation through implementing integrated platforms supported by Presidential Regulation on hajj-umrah digital transformation. The main contribution of this article lies in a holistic approach that integrates technology, diplomacy, and governance aspects in policy solutions towards Golden Indonesia 2045.